2017
DOI: 10.5296/jpag.v7i3.11657
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Building as Accelerator for Improving Autonomous Region Recently Knows as (DOB): Case Study in Seluma Distrcit Bengkulu Province, Indonesia

Abstract: The research aims to explore how capacity development of local government institution in Seluma district as the coordinator of Autonomous Region Recently known as DOB. This research background is lack capacity of government institution in Seluma district is improved poverty range amount 21,22%, the IPM lack, social environment isn't conducive, government management index lowly. This case indicates incapacity of DOB management organizer while this capacity building program is a strategy that can be implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Therefore, strengthening the capacity of apparatus HR is absolutely necessary so that institutional performance can be achieved in accordance with the objectives . The most vital institutional elements to be developed are the Apparatus HR elements (Darmi, Suwitri, Yuwanto & Sundarso, 2017). Based on the above studies, it is confirmed that HR is a person who plays an important role in the success of organizational management.…”
Section: ‹ 70 ›mentioning
confidence: 77%
“…Therefore, strengthening the capacity of apparatus HR is absolutely necessary so that institutional performance can be achieved in accordance with the objectives . The most vital institutional elements to be developed are the Apparatus HR elements (Darmi, Suwitri, Yuwanto & Sundarso, 2017). Based on the above studies, it is confirmed that HR is a person who plays an important role in the success of organizational management.…”
Section: ‹ 70 ›mentioning
confidence: 77%
“…Sumber daya manusia yang mempunyai sangat mendukung berjalannya suatu program pemerintah kabupaten menjadi program yang berhasil. SDM yang tinggi membuat suatu program pemerintahan menjadi mudah untuk menyentuh lapisan masyarakat terendah tentu menjadi tujuan penting dari sebuah program (Darmi, 2017).…”
Section: Sumber Dayaunclassified
“…A notion stated by Grindle (M. S. Grindle, 2011;Milen, 2001) places human resource capacity development as a priority in the capacity building program, which needs to be considered by the local government. HR-State Civil Apparatus is very important for institutions/organizations because it supports the performance of the institution through work, talent, creativity, and a fundamental role in achieving the vision and mission of an institution/organization (Darmi, Suwitri, Yuwanto, & Sundarso, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of human resources (Village Apparatus) who have a qualified capacity can be the key to solving problems in improving organizational performance (Darmi et al, 2017;Sunarsi, 2019), Likewise, the management of village funds requires the capacity of village apparatus resources. In addition, the management of village funds requires community participation (Hulu, Harahap, & Nasution, 2018).…”
Section: Introductionmentioning
confidence: 99%